FRI0097 Expression of uncoupling protein-1 in subcutaneous fat reduces the total cholesterol level and cardiovascular risk in female ra pateints. (12th June 2018) - Lyngfelt, L.I.; Erlandsson, M.C.; Nadali, M.; Andersson, K.M.; Silfverswärd, S.T.; Pullerits, R.; Bokarewa, M.I.
Abstract : Objectives: To improve understanding of fat-related molecular mechanisms behind the increased cardiovascular (CV) morbidity in patients with rheumatoid arthritis (RA). Methods: Transcription of uncoupling protein 1 (UCP1) was measured in the subcutaneous fat tissue and serum levels of lipoproteins, adipokines, and inflammation markers in 185 middle-aged female patients (mean age 51 years) with RA and compared between the groups stratified by the total cholesterol (TC) levels and the body mass index (BMI). The risk of dying of CV disease within 5 years was calculated electronically using the strategy proposed by Pocock et al. 1 Results: CVR was highest (risk score 27.76, 5 year CVR 0.67%) in the patients combining high TC (>5.1 mmol/L) and high BMI (>25 kg/m2), while those with low levels of TC and BMI had lowest CVR (risk score 10.82, CVR 0.11%). CVR was significantly decreased if either TC (TC lo BMI hi ) or BMI (TC hi BMI lo ) was low (p=0.017 and p=0.014, respectively). With the exception of TC lo BMI lo group, these groups had no difference with respect to age, disease duration, inflammation defined by serum IL6 and IL1, and disease activity measured by DAS28. TC lo BMI hi patients had an overall increase in fat expression of UCP1 (p=0.047) that has the cholesterol lowering capacity and may explain low TC levels in this group. In contrast, TC hi BMI lo patients had high prevalence of cases with unmeasurable UCP1 expression and higher levels of serum adiponectin (p=0.053) and HDL (p<10–5). Measurable expression of UCP1 was found in 79%. In total cohort, the patients with measurable UCP1 had higher inflammation and RA activity presented by IL-6 (p=0.0001), IL1b (p=0.037) and DAS28 (p=0.0086), compared to those with no UCP1 expression. TC lo BMI hi patients had an overall increase in fat expression of UCP1 (p=0.047) and lowest prevalence of cases with no UCP1 expression (6.2%). Conclusions: The study shows that UCP-1 expression in subcutaneous fat may be a CV protective mechanism in RA patients. The inflammation seems to be the driving force of UCP1 expression in RA. Reference: [1] Pocock SJ, McCormack V, Gueyffier F, Boutitie F, Fagard RH, Boissel JP. A score for predicting risk of death from cardiovascular disease in adults with raised blood pressure, based on individual patient data from randomised controlled trials. BMJ2001;323:75–81. Disclosure of Interest: None declared